Evaluation of Sport Psychology Knowledge of Coaches at the Buleleng Volleyball Academy (ABVB) - Wasti Danardani; Syarif Hidayat; Made Agus Dharmadi; Suwiwa, I Gede (Mimbar Ilmu, 2023)
Currently, the program contained in the training periodization focuses on physical training programs, techniques, and tactics for playing volleyball. However, the psychological condition is to blame if an athlete's performance fails. The generational difference between coaches and athletes greatly disrupts interactions, so a unique approach is needed that touches the psychological side of athletes in providing training and improving performance. This research aims to describe the level of understanding of coaches at the Buleleng Volleyball Academy (ABVB) regarding the psychology program of training periodization. This research is a descriptive analysis research, with 12 ABVB trainers as research subjects. Data were collected through observation and survey techniques with research instruments using two questionnaires. The first questionnaire determines the role of psychology in sports, and the second examines the coach's ability to implement psychology in training programs. Data analysis with data triangulation. This research was carried out during the Covid-19 pandemic, so it was carried out via Google Forms. The research results show that coaches understand the role of sports psychology but need to learn the form of training given to athletes. The conclusion is that ABVB coaches own sport psychology knowledge but have yet to apply it in handling athletes, so strengthening is needed to make coaches better at using it in training.